2004
DOI: 10.1644/ber-029
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Genetic Analysis of the Texas State Bison Herd

Abstract: The Texas State Bison Herd is directly descended from the herd assembled from 5 wild-caught bison by Charles Goodnight in the 1880s. In 1997, 36 bison were used to establish a herd at Caprock Canyons State Park. To aid in the development of a long-term genetic conservation plan for this population, we examined and analyzed allelic variation at 54 microsatellite loci representing each of the nuclear chromosomes in the bison genome. The current Texas State Bison Herd population exhibits low genetic diversity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
(42 reference statements)
1
28
0
1
Order By: Relevance
“…The integument of gastropods produces significant amounts of mucus and proteineous fluid for their locomotion and protection against predators (Luchtel and Deyrup-Olson 2001). We used this property of terrestrial molluscs to sample mucus using FTA cards (patented by Whatman), a commercially available product already tested on several species in various taxonomic groups (Halbert et al 2004;Johanson et al 2009;Signorovitch et al 2005). This sampling system proves to be of limited disturbance for the specimens, very handy and fast in the field because the sampling process is simple and does not require any additional chemical products.…”
Section: Introductionmentioning
confidence: 99%
“…The integument of gastropods produces significant amounts of mucus and proteineous fluid for their locomotion and protection against predators (Luchtel and Deyrup-Olson 2001). We used this property of terrestrial molluscs to sample mucus using FTA cards (patented by Whatman), a commercially available product already tested on several species in various taxonomic groups (Halbert et al 2004;Johanson et al 2009;Signorovitch et al 2005). This sampling system proves to be of limited disturbance for the specimens, very handy and fast in the field because the sampling process is simple and does not require any additional chemical products.…”
Section: Introductionmentioning
confidence: 99%
“…Buffalo DNA generated from whole blood was extracted via the phenol-chloroform method (6). DNA from bison was extracted from hair as previously described (7) and cattle DNA was extracted from semen straws (8).…”
Section: Dna Samplesmentioning
confidence: 99%
“…Although bison and domestic cattle are classified into different genera (Bison and Bos) and are estimated to have diverged 1.0-1.5 million years ago (Hartl et al 1988;Wall et al 1992;Ritz et al 2000), they still have the same number of chromosomes (m ¼ 30), the same chromosome banding patterns (Basrur and Moon 1967;Ying and Peden 1977), and a highly similar autosomal gene content and order (Schnabel et al 2003). Interbreeding between bison and domestic cattle can result in fertile offspring, and modern technologies have been used to detect domestic cattle genetic introgression in many extant bison populations (Polziehn et al 1995;Ward et al 1999;Ward 2000;Halbert et al 2005).Although the recently enriched bovine linkage map (Ihara et al 2004) has become a critical resource in the dissection of bovine quantitative traits including those of bison, only a few studies have reported microsatellite variation in North American bison (Momens et al 1998;Wilson and Strobeck 1999;Ward 2000;Halbert 2003;Schnabel et al 2003;Halbert et al 2004). Moreover, only one QTL genome scan has so far been reported in bison (Schnabel et al 2003); these investigators used a linkage map of 292 microsatellite markers spanning all 29 autosomes.…”
mentioning
confidence: 99%
“…Bison sampled from the FN herd included only calves from the 2002 roundup, from which height data are not available. DNA extraction from hair and whole blood samples, multiplex polymerase chain reaction design, and microsatellite analyses were performed as previously described (Halbert 2003;Halbert et al 2004). Sixty microsatellite marker loci distributed throughout the bison genome were scored for each sample.…”
mentioning
confidence: 99%
See 1 more Smart Citation